KEPATUHAN PENDERITA TUBERCULOSIS PARU DALAM MENJALANI PENGOBATAN - Ainun Fadhila; Rahmi Kurnia Gustin (Jurnal Kesehatan - STIKes Prima Nusantara, 2019)
Tuberculosis (TB) was a directly infectious disease caused by Mycobacterium Tuberculosis. TB incidence in the world varies between 275 cases / 100,000 population / year. The purpose of this study was to determine the factors related to the compliance of pulmonary TB patients undergoing treatment in the Puskesmas Working Area Rao Pasaman Regency 2018. The research method using descriptive method Analitik with the design approach of Cross-Sectional, the study began in March- 2018 in the working area of Pus Kesmas Rao, Pasaman Regency. The population in this study were 109 respondents. The sample in this study were 52 respondents with the proportional random Sampling technique, then the data is processed using the Chi-Square test. The results showed that knowledge obtained p-value 0, 002 (p <0, 05), the role of health workers obtained p-value 0,469 (p> 0, 05), family support obtained p-value 0, 021 (p <0,05), the role of PMO obtained p-value 0,002 ( p <0, 05) Advice from this study is directed to the puskesmas, to be more supportive, reminding and providing knowledge about benefits from compliance with consuming OAT to all TB patients who were recorded for treatment at the Rao Health Center in Pasaman Regency.